PERBEDAAN EFEKTIVITAS TEHNIK DISTRAKSI AUDIOVISUAL MENONTON KARTUN DAN BERMAIN PUZZLE TERHADAP KECEMASAN ANAK PRASEKOLAH SAAT MENJALANI TERAPI NEBULIZER - Ida Ayu Intan Widhyantari (Jurusan Keperawatan Poltekkes Kemenkes Makassar, 2022)
Children with acute respiratory infections usually require special treatment procedures in the hospital, so children must undergo various treatment procedures that usually cause anxiety which can interfere the delivery of therapy during the child's hospitalization if the anxiety was not properly managed. Puzzle games and audiovisual media can be used as distraction techniques to control children's anxiety. This study aims to determine the differences in the effectiveness of the audiovisual intervention watching cartoons and playing puzzles on preschool children's anxiety when nebulization therapy was administered in the Cilinaya Room of RSD Mangusada, Bali Province.This study is a quasy experiment study with a pretest and a posttest with control group, in which a total of 60 samples were selected by simple random sampling and divided into two groups. Data were collected using research instruments in the form of observation sheets with facial image scale and analyzed using Wilcoxon and Mann Whitney test. The results showed that the audiovisual intervention of watching cartoons was significantly more effective in reducing children's anxiety when using a nebulizer than playing puzzle therapy in the Cilinaya room, RSD Mangusada (p-value = 0.010). Nurses are expected to be able to use appropriate distraction techniques to control children's anxiety during nebulizer therapy.